Komunikasi Interpersonal Dalam Membentuk Self Confidence Pada Anak Di Kampung Pemulung Sarmili Jurang Mangu - Nasichah; Alda Okti Ramadini; Alfiyyah (CV. ITTC INDONESIA, 2024)
This research aims to describe the influence of interpersonal communication on the development of self confidence among children in Kampung Pemulung Sarmili, Jurang Mangu, South Tangerang. Interpersonal communication, involving face-to-face interactions between individuals, plays a crucial role in shaping children's character and personality, particularly within low social and economic environments. Through qualitative methods with a phenomenological approach, this study explores children's experiences of interpersonal communication and the role of parents and volunteer mentors in enhancing their self confidence. The research findings indicate that positive communication and emotional support from adults are pivotal in boosting children's self confidence. The theoretical and practical implications underscore the importance of developing intervention strategies and educational approaches that support positive development in similar environments. Concrete steps such as positive communication training for parents and the development of social skills among children are recommended to create a more positive and inclusive learning environment.